Vulnerability and Resilience under Effects of Tsunamis: Case of Industrial Plants - Mebarki, Ahmed; Willot, Adrien; Reimeringer, Mathieu; Jerez Barbosa, Sandra Rocio; Prod’hommeb, Gaëtan (Science Direct, 2014)
The resilience approach represents a unified and integrated framework for the restoration process following disasters. Under given resilience parameters values, a resilient system is able to recover and be strengthened within a defined recovery period; otherwise, it is a non-resilient system. This paper considers different structures and focuses on several parameters which govern resilience together with their mechanical vulnerability under various hazards. A new method of theoretically measuring resilience, its link with mechanical vulnerability and its sensitivity analysis are investigated for industrial plants under the effects of flood and tsunami hazards: -Coastal industrial plants under the effects of a tsunami hazard: structural failure in tanks results from buoyancy (uplift), overturning, sliding by shear effect, excessive bending, or buckling. -Vulnerability and fragility curves are developed for various tanks of small and large sizes.

El enfoque de la resiliencia representa un marco unificado e integrado para el proceso de restauración tras las catástrofes. Bajo determinados valores de los parámetros de resiliencia, un sistema resiliente es capaz de recuperarse y fortalecerse dentro de un periodo de recuperación definido; de lo contrario, es un sistema no resiliente. En este artículo se estudian diferentes estructuras y se centran en varios parámetros que rigen la resiliencia, junto con su vulnerabilidad mecánica ante diversos peligros. Se investiga un nuevo método de medición teórica de la resiliencia, su relación con la vulnerabilidad mecánica y su análisis de sensibilidad para plantas industriales bajo los efectos de los peligros de inundación y tsunami: -Plantas industriales costeras bajo los efectos de un peligro de tsunami: el fallo estructural en los tanques se produce por flotación (levantamiento), vuelco, deslizamiento por efecto de cizallamiento, flexión excesiva o pandeo. -Se desarrollan curvas de vulnerabilidad y fragilidad para diversos tanques de pequeño y gran tamaño. Traducción realizada con la versión gratuita del traductor www.DeepL.com/Translator
Keywords: Tsunamis; Resiliencia; Curvas de esfuerzo-deformación; Stress-strain curves; Edificios industriales; Industrial buildings; Zonas de riesgo de tsunami; Tsunami hazard zones; Tanques de almacenamiento; Storage tanks; Resilience; Vulnerability; Fragility; Hazard; Risk; Industrial plants; Metal tanks